2006
DOI: 10.1136/oem.2006.027151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of parental reports of smoking and residential air nicotine concentrations in children

Abstract: Background: Using questionnaires to assess children's residential exposure to environmental tobacco smoke (ETS) may result in misclassification from recall and response bias. Questionnaire data have frequently been validated against urinary cotinine measurements, but rarely against actual measurements of residential air nicotine. Objective: To compare questionnaire reported smoking with air nicotine concentrations in a large population of children and with urinary cotinine levels in a subpopulation; and to ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 22 publications
2
44
1
Order By: Relevance
“…Several studies found that maternal recall of smoking during pregnancy is reliable even 10 to 30 years later. [27][28][29][30] Parental report of SHS has been found to be reliable in some [31][32][33] and was found to be underreported in children with asthma 34 ; therefore, although recall bias is possible for in utero and SHS exposures, this may have attenuated the risk estimates because children with asthma were more likely to be in the unexposed group. This potential bias could account for the lack of significant modification of the association between Arg16Gly and asthma by smoking exposures.…”
Section: Discussionmentioning
confidence: 80%
“…Several studies found that maternal recall of smoking during pregnancy is reliable even 10 to 30 years later. [27][28][29][30] Parental report of SHS has been found to be reliable in some [31][32][33] and was found to be underreported in children with asthma 34 ; therefore, although recall bias is possible for in utero and SHS exposures, this may have attenuated the risk estimates because children with asthma were more likely to be in the unexposed group. This potential bias could account for the lack of significant modification of the association between Arg16Gly and asthma by smoking exposures.…”
Section: Discussionmentioning
confidence: 80%
“…Parental report of smoking has been found to be reliable in some (42)(43)(44) and was found to be underreported in children with asthma (45).Therefore, although recall bias is possible for in utero and secondhand smoke exposures, this may have attenuated the risk estimates because children with asthma were more likely to be in the unexposed group. Because genotyping for the TGF-b1 SNPs is not used in diagnosing asthma, diagnostic bias or recall bias in reporting age at asthma onset and persistence of symptoms by first grade (used to determine asthma phenotypes) with respect to the studied SNPs is unlikely.…”
Section: Discussionmentioning
confidence: 86%
“…However, selfreported data are comparable with cord blood, urinary cotinine, or indoor air nicotine measurements. 22,23 Additionally, exposure information was collected at baseline, before onset of disease symptoms. Thus, any misclassification is likely to be nondifferential and would tend to underestimate the true association.…”
Section: Discussionmentioning
confidence: 99%